2007
DOI: 10.1016/j.ajo.2007.02.030
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Diagnosis of Microbial Keratitis

Abstract: Purpose-To evaluate the ability of ophthalmologists to predict the laboratory results of presumed microbial keratitis and to explore which findings might influence diagnostic prognostication. Design-Prospective cross-sectional study.Methods-Fifteen ophthalmologists completed study forms at the initial presentation of patients with presumed microbial keratitis. After predicting the category of microbial recovery, clinicians submitted corneal scrapings for masked laboratory processing. The relative effects of oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
112
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(118 citation statements)
references
References 15 publications
5
112
0
1
Order By: Relevance
“…Dahlgren et al [5] reported that clinical examiners correctly predicted the presence or absence of microbial recovery in 79 (76%) of 104 ulcerative keratitis cases. The positive predictive value of clinical diagnosis was 45% (95% confidence interval 17-77%) for 13 FK [5] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dahlgren et al [5] reported that clinical examiners correctly predicted the presence or absence of microbial recovery in 79 (76%) of 104 ulcerative keratitis cases. The positive predictive value of clinical diagnosis was 45% (95% confidence interval 17-77%) for 13 FK [5] .…”
Section: Discussionmentioning
confidence: 99%
“…Since clinically it is difficult to establish a definitive diagnosis of FK, the final diagnosis is largely dependent upon a combination of clinical and microbiological results [5] .…”
Section: Introductionmentioning
confidence: 99%
“…This may result in corneal perforation, and Keratoplasty is performed. As the appearance of the ulceration for distinguishing fungal from bacterial ulcer is unreliable (45) and since resistant fungi have been reported (33,46), treatment on the basis of correct identification of pathogen by culture and determination of sensitivity could have better outcomes than empirical treatment with broad-spectrum antibiotics. Culture results are also critical to tailor therapy for patients who fail empirical therapy.…”
Section: Treatment Of Fungal Keratitismentioning
confidence: 99%
“…However, only 31 (42 %) were subcategorized properly, suggesting the notion that although infections can be detected, overlapping clinical features of the etiologic agents of keratitis makes it difficult to distinguish one from another. 22 Therefore, tissue sampling and culture continues to be an imperative utility in the diagnosis of fungal keratitis. Because of predilection of fungi to penetrate into deeper layers of the cornea, tissue swabbing is usually inadequate in confirming a fungal agent.…”
Section: Clinical Features and Diagnosismentioning
confidence: 99%